2021
DOI: 10.4269/ajtmh.20-0270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Progress and Risk Factors for Death from Severe Fever with Thrombocytopenia Syndrome: A Multihospital Retrospective Investigation in Anhui, China

Abstract: Knowledge of the clinical progress of severe fever with thrombocytopenia syndrome (SFTS) and the associated predictors of mortality is important for providing appropriate treatment in severe cases. A multihospital retrospective study was conducted in three SFTS-endemic cities, in 2018. Of the 208 SFTS-confirmed cases, there were 189 survivors and 19 deaths. The median age was 64 years; 104 (50.0%) patients were men, and 188 (90.4%) were farmers. Furthermore, 203 (97.6%) patients reported fever and 70 (33.7%) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…Previous studies have reported an incidence rate of central neurological complications in SFTS patients ranging from 19.1 to 76% ( Cui et al, 2015 ; Li et al, 2018 ; Park et al, 2018 ; Gong et al, 2021 ), consistent with the result of this study (37.4%). Cui et al (2015) reported that 19.1% of SFTS patients developed central neurological complications, which manifested as blurred mind, dysphoria, convulsion, drowsiness, and coma, with 44.7% of them dying.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies have reported an incidence rate of central neurological complications in SFTS patients ranging from 19.1 to 76% ( Cui et al, 2015 ; Li et al, 2018 ; Park et al, 2018 ; Gong et al, 2021 ), consistent with the result of this study (37.4%). Cui et al (2015) reported that 19.1% of SFTS patients developed central neurological complications, which manifested as blurred mind, dysphoria, convulsion, drowsiness, and coma, with 44.7% of them dying.…”
Section: Discussionsupporting
confidence: 93%
“…The diagnostic criteria for SFTS combined with central neurological complications ( Gai et al, 2012 ; Cui et al, 2015 ; Kato et al, 2016 ; Fei et al, 2021 ; Gong et al, 2021 ): patients who developed one or more of the following symptoms: paroxysmal involuntary muscle and limb tremor; personality and behavior changes, including irritability, apathy, dysphoria and unresponsiveness; cognitive impairment, including decline in orientation, memory and calculation, inability to accurately answer questions, inability to cooperate with simple commands, inability to perform fine exercise and aphasia, as well as language communication impairment; impaired consciousness, including drowsiness, lethargy, confusion, delirium, and coma; and convulsions or seizures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFTS has a wide range of clinical manifestations, from hyperthermia, thrombocytopenia, leukopenia, and gastrointestinal symptoms to hemorrhage, altered consciousness, and multiple organ dysfunction. It has a high mortality rate of about 11-30%, and aging, high viral load, and neurological manifestations are risk factors associated with poor prognosis [2,5,[11][12][13]. Due to its high lethality and potential for pandemic transmission, SFTS is classified as a nationally reported disease in China, and the World Health Organization (WHO) listed SFTS as one of the top 10 priority infectious diseases in urgent need of investigation in 2017 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Liver damage: Patients with SFTS often show symptoms of impaired liver function and the degree of hepatic impairment was correlated with the severity of the clinical course ( Gai Z. T. et al., 2012 ; Cui et al., 2014 ; Nakano et al., 2017 ; Gong et al., 2021 ). An in vitro study found that SFTSV could replicate efficiently in HepG2 and induce significant secretion of pro-inflammatory cytokines and chemokines in HepG2 cells, such as IL-6, IL-8, TNF-α, as well as CC chemokine ligand-5, macrophage inflammatory protein-3α, and IP-10, promoting virus replication and further infection-induced apoptosis ( Sun Q. et al., 2015 ).…”
Section: Host Immune Responsementioning
confidence: 99%